(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the impacts caused by the rupture of the Fundão Barragem in Mariana, Minas Gerais, Brazil, from the perspective of the national media. To identify the impacts, a qualitative, documentary type research was chosen. The data were collected from reports published in the spoken and written media, from October 2015 to March 2016 and documents published on the topic, in the same period. 16 reports and 04 official documents were analyzed from the checklist and matrices. Under the conditions studied, 16 impacts were identified. Of these, only one was positive, solidarity among residents. Among the negative impacts identified, social ones prevailed, followed by economic and environmental ones. According to national media, the tragedy was caused by the negligence of the company Samarco, which did not carry out the proper maintenance on the dam. In the documents studied, it was found that the fault was not only with the company, the bodies responsible for inspection also had their collaboration. Residents said it was the fault of the company that did not carry out the maintenance and did not warn them about the flood of mud. It was found that the news were centered on the anthropocentric vision that has capitalism as its economic model, however, the most serious impacts are related to the environment, as they involve the well-being and maintenance of the species Homo sapiens itself. Pondering the domino effect, several ecosystems were damaged, demanding new ecological niches, although the highlights of the national media were directed to the social environment, of an economic nature.